Portret Wiktora Zbyszewskiego w kompozycji Jana Czubskiego – przypomnienie sylwetki rzeszowskiego patrioty - Pięta-Kowalik, Sybilla (Dydaktyka Polonistyczna, 2018)
This paper describes Rzeszów between XIX and XX century. It presents Jan Czubski, a composer working in this city before the war, as well as his work regarding Wiktor Zbyszewski – a local patriot who had a great involvement in Rzeszów’s stride forward. The article concentrates on words in the work as well as axiology concerning residents’ attitudes toward local cultural activities.